ANALYSIS AND IMPLEMENTATION OF HALAL LEBELIZATION: CASE STUDY IN THE FOOD AND BEVERAGE INDUSTRY - Mahlel Mansur (Jurnal Penelitian Progresif, 2023)
This research aims to analyze and implement halal labeling in the context of the food and beverage industry. Halal labeling is the process of giving halal labels to products that meet the halal requirements set by the competent halal authority. A case study was conducted to understand the process of implementing halal certification in the food and beverage industry, as well as its impact on producers, consumers and the market as a whole. The research method used in this study is a qualitative approach by collecting data through in-depth interviews with food and beverage producers, halal authorities, and consumers involved in the halal certification process. Apart from that, an analysis of documents related to applicable halal regulations and standards was also carried out. The research results show that the implementation of halal labeling provides significant benefits for food and beverage producers. In increasingly fierce competition, the halal label can increase consumer confidence, expand the market and improve the company's reputation. However, implementing halal labeling also poses challenges, such as halal certification costs, meeting strict requirements, and operational adjustments. From a consumer perspective, the halal label is an important factor in making purchasing decisions. Consumers who pay attention to halal aspects look for halal labels as a guarantee of product quality and safety. This research also highlights the importance of consumer education and awareness regarding halal labeling, as well as government efforts to increase supervision and enforcement of halal regulations. Overall, this research provides insight into the analysis and implementation of halal labeling in the food and beverage industry. The results of this research can serve as a guide for producers in understanding the benefits and challenges associated with halal labeling, as well as provide a basis for developing policies and strategies related to halal aspects of products.